Students’ Attitudes Toward Local Languages: The Case Of Indonesian High School Students - Alamsyah, Aam (Indonesian Scientific Publication, 2024)
This study examines the status of Indonesian local languages, emphasizing their role in identity preservation and linguistic diversity across the archipelago. Despite their cultural significance, local languages often receive less appreciation than international languages, which are perceived to have greater socioeconomic value. Current research on Indonesian local languages is limited, typically focusing on linguistic aspects in isolation. This study takes a broader approach, considering factors such as pedagogy, employability, and publicity. A mixed-method approach was used, including questionnaires, interviews, and documentary analysis to gather data from 60 high school students. The results show that, despite the absence of local language instruction, students held positive attitudes toward their local languages and actively used them outside of school. However, regarding employability, students believed that proficiency in local languages would not significantly improve their job prospects. They also recognized the importance of local language visibility in media, as it could stimulate public interest and enhance the economic value of these languages. The study highlights the need for a more comprehensive understanding of the factors influencing local language use and its potential benefits.